2022
DOI: 10.1155/2022/3577715
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Milk Contamination, Associated Risk Factors, and Drug Sensitivity Patterns among Isolated Bacteria from Raw Milk of Borena Zone, Ethiopia

Abstract: Background. The contamination of raw milk depends on the number and type of organisms that can cause health risks, which can be judged by the presence of microorganisms and bacterial pathogens. This study evaluated bacterial contamination, the risk factor, and drug sensitivity patterns. Methods. A cross-sectional study was carried out on conveniently selected 95 milk producers. Data were collected using the structured pretest questionnaire and the observation control list. Subsequently, 15 to 20 ml of milk sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
2
8
1
Order By: Relevance
“…On the other hand, low moisture content means low water activity, which leads to a reduction in microbial development and, as a result, a longer shelf life for the milk sample. The findings in this study are consistent with the information collected by other researchers [30,31]. Shiv., et al [30] found that the proximate composition of the milk samples showed that the moisture content of the milk samples were 86.24%, 87.35%, and 83.92%, which fell within the range of 81% to 89.5% that the International Dairy Foods Association has approved for the proximate composition of milk.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, low moisture content means low water activity, which leads to a reduction in microbial development and, as a result, a longer shelf life for the milk sample. The findings in this study are consistent with the information collected by other researchers [30,31]. Shiv., et al [30] found that the proximate composition of the milk samples showed that the moisture content of the milk samples were 86.24%, 87.35%, and 83.92%, which fell within the range of 81% to 89.5% that the International Dairy Foods Association has approved for the proximate composition of milk.…”
Section: Discussionsupporting
confidence: 93%
“…The increment of bacterial load could be attributed to the contamination of the milk from production to consumer by different factors like the pooling of milk from different sources together with unhygienic handling [51]. The overall mean coliform count detected in the bulk tank milk samples in the current study was 4.09 log10 CFU/mL, which is relatively lower than the 6.54 ± 1.53 log10 CFU/m count reported by Aliyo and Teklemariam [52] from the southern pastoral areas of Ethiopia. Coliform count in milk managed under poor hygienic conditions was signi cantly (p < 0.05) higher than under good, and moderate, hygienic conditions, suggesting that the practice of production of milk under poor hygienic conditions favors the contamination with coliform and could be responsible for the high observed counts.…”
Section: Enumerations Of Coliformcontrasting
confidence: 53%
“…This allows them to spread quickly across an environment, and cause contamination. [ 30 ] The mere existence of these organisms in a sample of milk has to be taken quite seriously in order to ensure that the quality of the milk is protected and maintained. Milk samples may include coliform bacteria for a variety of reasons; some of these reasons include improper handling, inadequate sanitation in the area around the cow barn, and contamination of the sample by unclean water.…”
Section: Resultsmentioning
confidence: 99%